Learning from failures : decision analysis of major disasters - Labib, Ashraf (Elsevier Science, 2014)
Learning from Failures provides techniques to explore the root causes of specific disasters and how we can learn from them. It focuses on a number of well-known case studies, including: the sinking of the Titanic; the BP Texas City incident; the Chernobyl disaster; the NASA Space Shuttle Columbia accident; the Bhopal disaster; and the Concorde accident. This title is an ideal teaching aid, informed by the author's extensive teaching and practical experience and including a list of learning outcomes at the beginning of each chapter, detailed derivation, and many solved examples for mo.